2021
DOI: 10.3390/healthcare9080932
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Simulated Leg-Length Discrepancy on the Dynamic Parameters of the Feet during Gait—Cross-Sectional Research

Abstract: Background: The effect of Leg-Length Discrepancy (LLD) on dynamic gait parameters has been extensively discussed. Podobarography is the study of foot-to-ground pressure distribution. It has been used to test plantar footprint deviations that could reveal pathology. Purpose: The aim of this study is to determine the effects of simulated LLD on dynamic gait parameters measured with a pressure platform in healthy subjects. Methods: Thirty-seven healthy subjects participated in observational cross-sectional resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Furthermore, examination of the leg-length discrepancy of the limb, which was not included in this study, is likely to bear an impact on changes of plantar pressure associated with the balance of the centers of gravity in CP patients. As shown in the studies by Pereiro-Buceta et al [ 45 ], the increased discrepancy of leg-length resulted in asymmetric foot-loading with an increased mean and peak pressure on the short limb and decreased plantar loads on the long limb. A greater discrepancy may lead to an increased stance time on the long limb.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, examination of the leg-length discrepancy of the limb, which was not included in this study, is likely to bear an impact on changes of plantar pressure associated with the balance of the centers of gravity in CP patients. As shown in the studies by Pereiro-Buceta et al [ 45 ], the increased discrepancy of leg-length resulted in asymmetric foot-loading with an increased mean and peak pressure on the short limb and decreased plantar loads on the long limb. A greater discrepancy may lead to an increased stance time on the long limb.…”
Section: Discussionmentioning
confidence: 96%
“…The asymmetric loading of bones, joints, and soft tissue structures [ 5 , 10 ] caused by deviation of the mechanical axes of the lower limbs and the resulting compensatory postural responses, such as pelvis obliquity [ 11 , 12 ] and torsion of the innominate bones [ 13 ], as well as lumbar scoliosis and hypo- or hyperlordosis [ 9 , 14 , 15 ], that occur due to LLD are thought to be largely responsible for these problems. Research has shown that the significant although controversial effects of postural as well as kinematic and kinetic compensatory responses induced by LLD on body function [ 16 , 17 , 18 , 19 , 20 ] have led authors to question the magnitude of LLD that should be considered clinically significant. An extensive systematic review of the existing literature revealed that while some researchers state that structural LLD as low as 1.0 cm may need to be corrected as it can cause complications in the human body in the long term (e.g., low back pain [ 21 ], plantar fasciitis [ 6 ], knee osteoarthritis [ 22 ]), others report that differences between leg lengths of up to 6.0 cm have no significant effect on human function (e.g., ground reaction forces, energy consumption) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The peak pressure value is defined as the highest pressure and frequently reported in plantar pressure studies 6 9 . Increases in peak pressure have been found to be particularly related to the development of DFUs due to the presence of peripheral neuropathy 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%